Development and validation of software for rapid performance estimation of small RPAS. (August 2017) - Aliaga-Aguilar, Hugo; Cuerno-Rejado, Cristina
Highlights: An aerodynamic RPAS performance estimation model has been developed and validated with twelve commercially available RPAS The aerodynamic model estimates include pitching moment and drag polar, which were validated with existing literature. The model presented an average error of 8.11%, which is promising for preliminary analysis of aerodynamics within MDO. All the calculations were performed in less than 1.5 s per aircraft. Abstract: There is a high demand for small unmanned aircraft for a wide variety of missions. The relatively limited experience and resources of new commercial companies renders it almost impossible for them to tackle a complete design process with the same quality and results as bigger and more experienced companies. We aim to develop a full rapid design methodology software for such aircraft and present the first step in the process in the form of a performance estimation model. This model is tested with data from ten different commercially available RPAS, as well as two additional RPAS for aerodynamic validation. A comparison between the results obtained by means of this model and the manufacturers' data is presented.